Estrogen Receptor (ESR1) mRNA Expression and Benefit From Tamoxifen in the Treatment and Prevention of Estrogen Receptor–Positive Breast Cancer - Kim, Chungyeul (American Society of Clinical Oncology, 2011)
PURPOSE: Several mechanisms have been proposed to explain tamoxifen resistance of estrogen receptor (ER) –positive tumors, but a clinically useful explanation for such resistance has not been described. Because the ER is the treatment target for tamoxifen, a linear association between ER expression levels and the degree of benefit from tamoxifen might be expected. However, such an association has never been demonstrated with conventional clinical ER assays, and the ER is currently used clinically as a dichotomous marker. We used gene expression profiling and ER protein assays to help elucidate molecular mechanism(s) responsible for tamoxifen resistance in breast tumors. PATIENTS AND METHODS: We performed gene expression profiling of paraffin-embedded tumors from National Surgical Adjuvant Breast and Bowel Project (NSABP) trials that tested the worth of tamoxifen as an adjuvant systemic therapy (B-14) and as a preventive agent (P-1). This was a retrospective subset analysis based on available materials. RESULTS: In B-14, ESR1 was the strongest linear predictor of tamoxifen benefit among 16 genes examined, including PGR and ERBB2. On the basis of these data, we hypothesized that, in the P-1 trial, a lower level of ESR1 mRNA in the tamoxifen arm was the main difference between the two study arms. Only ESR1 was downregulated by more than two-fold in ER-positive cancer events in the tamoxifen arm (P < .001). Tamoxifen did not prevent ER-positive tumors with low levels of ESR1 expression. CONCLUSION: These data suggest that low-level expression of ESR1 is a determinant of tamoxifen resistance in ER-positive breast cancer. Strategies should be developed to identify, treat, and prevent such tumors.